ABNORMAL ALDOSTERONE PHYSIOLOGY AND CARDIO-METABOLIC RISK FACTORS - Vaidya, Anand (2013)
Abnormal aldosterone physiology has been implicated in the pathogenesis of cardio-metabolic diseases. Single aldosterone measurements capture only a limited range of aldosterone physiology. New methods of characterizing aldosterone physiology may provide a more comprehensive understanding of its relationship with cardio-metabolic disease. We evaluated whether novel indices of aldosterone responses to dietary sodium modulation, the Sodium-modulated Aldosterone Suppression-Stimulation Index (SASSI for serum and SAUSSI for urine), could predict cardio-metabolic risk factors. We performed cross-sectional analyses on 539 subjects studied on liberal (LIB) and restricted (RES) sodium diets with serum and urinary aldosterone measurements. SASSI and SAUSSI were calculated as the ratio of aldosterone on LIB (maximally suppressed aldosterone) to aldosterone on RES (stimulated aldosterone) diets, and associated with risk factors using adjusted regression models. Cardio-metabolic risk factors associated with either impaired suppression of aldosterone on LIB diet, or impaired stimulation on RES diet, or both; in all of these individual cases, these risk factors associated with higher SASSI or SAUSSI. In the context of abnormalities that comprise the metabolic syndrome (MetS), there was a strong positive association between the number of MetS components (0–4) and both SASSI and SAUSSI (P<0.0001) that was independent of known aldosterone secretagogues (angiotensin II, corticotropin, potassium). SASSI and SAUSSI exhibited a high sensitivity in detecting normal individuals with zero MetS components (86% for SASSI and 83% for SAUSSI). Assessing the physiologic range of aldosterone responses may provide greater insights into adrenal pathophysiology. Dysregulated aldosterone physiology may contribute to, and/or result from, early cardio-metabolic abnormalities.